Self-selection and socialisation effects of business and legal studies - Tim Rosengart; Bernhard Hirsch; Christian Nitzl (Journal of Business Economics, 2020)
To explore the effect of business and legal studies on the resolution of trade-offs between efficiency considerations and fairness concerns, we distributed a survey with three decision cases to freshman and senior business and law students. Our results show that business students, in direct comparison with subjects who study law, make decisions more in accordance with economic theory. Studying business administration leads to decisions that are based more on efficiency criteria, while legal education appears to lead individuals making decisions that are more based on social criteria. Our findings reveal the impact of self-selection and socialization effects on decision making. For business ethics education, this result matters because moral decision making can be influenced during studies.
Keywords: 650; University education; Self-selection; Socialisation; Economic decision making; A220